Tetrahedral node for Transmission-Line Modeling (TLM) applied to Bio-heat Transfer - Milan, Hugo F.M.; Gebremedhin, Kifle G. (Computers in biology and medicine, 2016)
Transmission-Line Modeling (TLM) is a numerical method used to solve complex and time-domain bio-heat transfer problems. In TLM, parallelepipeds are used to discretize three-dimensional problems. The drawback in using parallelepiped shapes is that instead of refining only the domain of interest, a large additional domain would also have to be refined, which results in increased computational time and memory space. In this paper, we developed a tetrahedral node for TLM applied to bio-heat transfer that does not have the drawback associated with the parallelepiped node. The model includes heat source, blood perfusion, boundary conditions and initial conditions. The boundary conditions could be adiabatic, temperature, heat flux, or convection. The predicted temperature and heat flux were compared against results from an analytical solution and the results agreed within 2% for a mesh size of 69,941 nodes and a time step of 5ms. The method was further validated against published results of maximum skin-surface temperature difference in a breast with and without tumor and the results agreed within 6%. The published results were obtained from a model that used parallelepiped TLM node. An open source software, TLMBHT, was written using the theory developed herein and is available for download free-of-charge. •TLM tetrahedral node removes the associated drawback with parallelepiped node.•TLM model can be used in solving heat transfer problems in biological systems.•Heat source, blood perfusion, and different boundary conditions are considered.•Validated against analytical solution and results from parallelepiped TLM node.•TLM computation was 1550x faster than analytical computation.